2021
DOI: 10.1038/s41598-021-98102-9
|View full text |Cite
|
Sign up to set email alerts
|

Vm-related extracellular potentials observed in red blood cells

Abstract: Even in nonexcitable cells, the membrane potential Vm is fundamental to cell function, with roles from ion channel regulation, development, to cancer metastasis. Vm arises from transmembrane ion concentration gradients; standard models assume homogeneous extracellular and intracellular ion concentrations, and that Vm only exists across the cell membrane and has no significance beyond it. Using red blood cells, we show that this is incorrect, or at least incomplete; Vm is detectable beyond the cell surface, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(55 citation statements)
references
References 46 publications
4
37
0
Order By: Relevance
“…A best-fit value for Ψ st,o of − 31 mV was previously obtained in control solutions 11 ; values under the other conditions described here are available in that work. If we assume that there is ion diffusion across the membrane, then alteration of these ion concentrations will determine the extent of transmembrane diffusion; if cytoplasmic ions equilibrate with the medium, then this expression would represent the ionic strengths across which the cytoplasm would equilibrate.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…A best-fit value for Ψ st,o of − 31 mV was previously obtained in control solutions 11 ; values under the other conditions described here are available in that work. If we assume that there is ion diffusion across the membrane, then alteration of these ion concentrations will determine the extent of transmembrane diffusion; if cytoplasmic ions equilibrate with the medium, then this expression would represent the ionic strengths across which the cytoplasm would equilibrate.…”
Section: Resultsmentioning
confidence: 81%
“…This yields the expression: where 1/κ is the Debye length; the number of ions per m 3 for a medium conductivity of 1 S m −1 , and A as defined in Eq. (11). V x was as before.…”
Section: Membrane Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…DEP has revealed circadian cycles in the electrical properties of RBCs ( Henslee et al, 2017 ; Beale et al, 2019 ; Beale et al, 2022 ) human as well as sub-2 h, ultradian rhythms in the RBCs of voles ( Hoettges et al, 2019 ). More recently, connections have been demonstrated between these DEP-derived electrical parameters and other electrical measures of cell function, such as the membrane potential (V m ) and the extracellular electrical potential (the ζ-potential) that regulates the way cells interact with other cells and biological entities in their immediate environment ( Hughes et al, 2021 ; Hughes et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric properties of a living cell membrane inside a microfluidic device are indicators of their physiological status, which is closely connected with cell state and function. Several previous studies have shown that changes in these dielectric properties are linked to processes such as ion channel activation [ 1 , 2 ]; membrane fusion; and budding and flip-flop [ 3 , 4 ], which contribute to the characterization of cell circadian rhythm [ 1 , 5 ]; cell progression [ 6 , 7 ]; cell viability [ 8 , 9 , 10 ]; and cell malignancy [ 11 , 12 ]. Recent advances in microfluidic and micro/nanotechnology have enabled the detection of cell membrane dielectric response at a whole-cell level, which makes it an attractive label-free biomarker candidate for discriminating cell populations for stem cell differentiation [ 13 , 14 ], leukocyte activation [ 15 ], and circulating tumor cell existence [ 16 ].…”
Section: Introductionmentioning
confidence: 99%